2000
DOI: 10.1046/j.1365-2141.2000.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted usage of T‐cell receptor α‐chain variable region (TCRAV) and T‐cell receptor β‐chain variable region (TCRBV) repertoires after human allogeneic haematopoietic transplantation

Abstract: Summary. We analysed T-cell receptor a-chain variable region (TCRAV) and T-cell receptor b-chain variable region (TCRBV) repertoires in peripheral blood mononuclear cells (PBMCs) from 34 recipients of allogeneic bone marrow transplantation (allo-BMT), seven of allogeneic peripheral blood stem cell transplantation and 19 of autologous peripheral blood stem cell transplantation using the quantitative microplate hybridization assay. TCR usage skewed at an early period (6±7 weeks) after BMT. The change was more ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
(24 reference statements)
5
33
0
Order By: Relevance
“…2,3 We also found that TCR usage appears to be limited, and that amino acid sequences frequently contain an arginine residue followed by acidic amino acid residues in the complementarity-determining region 3 (CDR3) of TCR-␤ chains containing BV24S1, suggesting that skewing of the TCRAV and TCRBV repertoires is antigen-driven. 1 These features of post-transplant T cell regeneration are similar to those during extrathymic differentiation of T cell progenitors and peripheral expansion of mature T cell populations, which have been demonstrated by murine bone marrow transplantation studies. 4 Extrathymic differentiation of T cell progeny in bone marrow generates TCR␥␦ ϩ and CD4 Ϫ CD8 Ϫ TCR␣␤ ϩ T cells.…”
mentioning
confidence: 59%
“…2,3 We also found that TCR usage appears to be limited, and that amino acid sequences frequently contain an arginine residue followed by acidic amino acid residues in the complementarity-determining region 3 (CDR3) of TCR-␤ chains containing BV24S1, suggesting that skewing of the TCRAV and TCRBV repertoires is antigen-driven. 1 These features of post-transplant T cell regeneration are similar to those during extrathymic differentiation of T cell progenitors and peripheral expansion of mature T cell populations, which have been demonstrated by murine bone marrow transplantation studies. 4 Extrathymic differentiation of T cell progeny in bone marrow generates TCR␥␦ ϩ and CD4 Ϫ CD8 Ϫ TCR␣␤ ϩ T cells.…”
mentioning
confidence: 59%
“…5,7 In addition, evidence indicates the stable clonal expansion of T lymphocytes after bone marrow transplantation. 30,31 Whether these clonally expanded T cells in blood recognize allogeneic, or microorganism-921 Table 5 Deduced Bone Marrow Transplantation derived antigens remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] We previously reported a skewing of repertoires of the T cell receptor-␤ chain variable region (TCRBV) and the TCR-␣ chain variable region (TCRAV) in recipients of allogeneic hematopoietic stem cell grafts from HLAmatched donors. 5 This results from the extensive clonal expansion of a limited number of T cells in the graft. 6 Skewed TCR repertoires accompany accumulation of the CD28 Ϫ fraction in both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations